A Review: Kombinasi Pupuk Kompos dan NPKMg sebagai Alternatif Pemupukan Ramah Lingkungan untuk Perkebunan - Nadhiya Luqyana; Ariyanti, Mira (Agriculture, 2025)
The plantation sector plays an important role in the Indonesian economy, but its productivity is still hampered by land degradation and inefficient use of production inputs. The combination of NPKMg inorganic fertilizer with compost fertilizer is seen as a balanced fertilization strategy that can improve soil fertility, nutrient availability, and plant growth. This article was compiled through a descriptive-qualitative literature review on the use of NPKMg and various types of compost in plantation commodities. The results of the study show that the interaction between the two has a significant effect on plant seedling growth parameters and has the potential to increase productivity while maintaining the sustainability of plantation land. Keywords: Balanced fertilization, sustainability, plantation